POLITIK ISLAM KONTEMPORER: ANALISIS HADIS TENTANG PEMIMPIN PELINDUNG RAKYAT - Prayogo, Agung; Siregar, Muhammad Nuh; Zalukhu, Deprichan Syahputra; Pia, Adi (IMTIYAZ: Jurnal Ilmu Keislaman, 2023)
This article presents an in-depth analysis of the hadith about protecting the people in the context of contemporary Islamic politics. The formulation of the problem involves the urgency of the leader's role as protector of the people, viewed from the perspective of Islamic ethics. The purpose of writing is to discuss and understand the implications of this hadith in modern political dynamics and seek a deeper understanding of the responsibility of leaders in maintaining the security and rights of the people. The research method used is Double Movement Hermeneutics, by detailing and analyzing the hadith as a conceptual basis. The research results show that this paper links these findings to contemporary Islamic political conditions where leadership that reflects ethical and moral values is an urgent need. The content in the hadith editorial is related to contemporary Islamic politics, including; principles of security and stability, principles, justice and human rights, finally law enforcement. This emphasizes the importance of leaders as protectors of the people, especially leaders who understand and understand the ethical principles contained in the Koran and Hadith which can be implemented in the world of politics.